Conductivity of Titanium(III) Soaps in Benzene-Cyclohexane Mixture - Verma, H.S.; Kumar , Vinod (Asian Journal of Chemistry, 2010)
In present work, the effects of temperature on the conductance behaviour of titanium (laurate, myristate, palmitate and stearate) in benzene + cyclohexane mixtures were studied. Attempts have been made to determine critical micelle concentration dissociation constant (K), molecular conductance and infinite dilution (λ∞) heat of dissociation (ΔHº) and activation energy of conductance (ΔEλ) of these soaps under different conditions.